BUNGA MATAHARI SEBAGAI SIMBOL CERIA DALAM KARYA LUKIS REALIS KONTEMPORER - Ayu Desmita; Abd. Hafiz (Serupa The Journal of Art Education, 2020)
The aim of making this final artwork is to provide information on social phenomena by visualizing sunflowers as a cheerful symbol in a contemporary realist painting style. So that everyone can get lessons and motivation from nature, while applying the technical skills of painting and deepening the concept of work. The method used in the final work is the preparation stage, the elaboration stage, the synthesis stage, the concept realization stage, the completion stage. So that there were ten works visualizing sunflowers with the following titles: The first work, "Optimist". Second, "Spirit". Third, "Friendly". Fourth, "Firm". Fifth, "Charismatic". Sixth, "Tough". Seventh, "Identical". Eighth, "Submit". Ninth, "Loyalty". Tenth, "Young soul".Kata kunci: Simbol , Bunga Matahari, Lukis Realis Kontemporer